PENDEKATAN SPIRITUAL SEBAGAI STRATEGI COPING IBU MENGHADAPI KECEMASAN DI MASA PANDEMI COVID-19 - Mayrina Eka Prasetyo Budi (Proceeding of Conference on Strengthening Islamic Studies in The Digital Era, 2021)
This research discusses the spiritual approach as a mother’s coping strategy in delaing with anxiety during the COVID-19 pandemic . The research subjects consisted of 24 mothers in Ponorogo District. This research is a descriptive qualitative research. The data obtained by using google form with closed questioned system and online interview. Data analysis uses triangulation of data sources. The results showed that respondents felt anxiety at the beginning of the COVID-19 pandemic until now. They feel anxious to leave the house and interact with other people. This anxiety can be controlled by spiritual activities such as dhikr, prayer, positive thinking, reading Al Qur’an and tawakal surrendering averything to Allah swt. The majority of respondents paid attention to health protocols very well as an effort to prevent the spread of the COVID-19 virus. Mothers try to thik positively that Allah will protect and the pandemi will end. It can be concluded that spiritual approaches make mothers able to manage their anxiety and bring peace of mind in the face of the COVID-19 pandemic. Key words: Spiritual;Anxiety ;The COVID-19 Pandemi